Supplementation of astaxanthin and vitamin E in feed on the development of gonads white shrimp broodstock Litopenaeus vannamei Boone 1931 - Maulana, Fajar; Arfah, Harton; Istifarini, Mita; Setiawati, Mia (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT The quality of white shrimp Litopenaeus vannamei broodstock can be improved through the addition of astaxanthin and vitamin E in the diet. This study aimed to determine the effect of administration of astaxanthin and vitamin E with different doses in the feed on the maturity gonad of prospective Pacific white shrimp broodstock. Supplementation of 0 mg/kg feed astaxanthin + 0 mg/kg feed vitamin E (control/A), 500 mg/kg feed astaxanthin (B), 350 mg/kg feed vitamin E (C), 500 mg/kg feed astaxanthin and 350 mg/kg feed vitamin E (D), and 250 mg/kg feed astaxanthin and 175 mg/kg feed vitamin E (E) were applied in feed formulation. Shrimp was fed 2% of body weight three times daily at 06.00 am, 13.00 pm, and 20.00 pm. The result showed that the optimum dose for survival, specific growth rate and maturity level of Pacific white shrimp broodstock was obtained in the combination of 175 mg/kg vitamin E and 250 mg/kg astaxanthin. The survival of shrimp by that treatment was 100.00±0.00%, specific growth rate 1.07±0.26%/day, the first level of gonad maturity growth was reached at day 14 (19.45±4.81%), the fourth level of gonad maturity was obtained at day 41, spawning rate 33.33±8.33%, fecundity 87,000±2,000 eggs, and hatching rate reached 49.00±1.53%. Keywords: astaxanthin, Litopenaeus vannamei, vitamin E ABSTRAK Peningkatan kualitas induk udang vaname Litopenaeus vannamei dapat dilakukan dengan penambahan vitamin E dan astaxanthin pada pakan. Tujuan penelitian ini adalah untuk mengevaluasi pengaruh pemberian astaxanthin dan vitamin E dengan dosis berbeda dalam pakan terhadap tingkat kematangan gonad calon induk udang vaname. Dosis yang digunakan adalah 0 mg/kg pakan astaxanthin + 0 mg/kg pakan vitamin E (kontrol/A), 500 mg/kg pakan astaxanthin (B), 350 mg/kg pakan vitamin E (C), 500 mg/kg pakan astaxanthin and 350 mg/kg pakan vitamin E (D), and 250 mg/kg pakan astaxanthin and 175 mg/kg pakan vitamin E (E). Pemberian pakan dengan penambahan vitamin E dan astaxanthin dilakukan sebanyak tiga kali, yaitu jam 06.00, 13.00, dan 20.00 WIB sebanyak 2% dari bobot udang. Hasil penelitian menunjukkan bahwa dosis optimum untuk sintasan, laju pertumbuhan spesifik, dan tingkat kematangan induk udang vaname diperoleh dengan kombinasi 175 mg/kg vitamin E dan 250 mg/kg astaxanthin. Kelangsungan hidup udang dengan perlakuan tersebut adalah 100,00±0,00%, laju pertumbuhan spesifik 1,07±0,26%/hari, tingkat kematangan gonad pertama dicapai pada hari ke 14 (19,45±4,81%), tingkat kematangan gonad keempat diperoleh pada hari ke 41, tingkat pemijahan 33,33±8,33%, fekunditas 87.000±2.000 telur, dan tingkat penetasan mencapai 49,00±1,53%. Kata kunci: astaxanthin, udang vaname Litopenaeus vannamei, vitamin E